Mapping the gene causing hereditary primary hyperparathyroidism in a Portuguese kindred to chromosome 1q22-q31. - Williamson, C; Cavaco, B; Jauch, A; Dixon, P; Forbes, S; Harding, B; Holtgreve-Grez, H; Schoell, B; Pereira, M; Font, A; Loureiro, M; Sobrinho, L; et al. (1999)
A Portuguese kindred with autosomal dominant isolated primary hyperparathyroidism (HPT) that was associated with parathyroid adenomas and carcinomas was investigated with the aim of determining the chromosomal location of this gene, designated HPTPort. Leukocyte DNA from 9 affected and 16 unaffected members and 7 parathyroid tumors from 4 patients was used in comparative genomic hybridization (CGH), tumor loss of heterozygosity (LOH), and family linkage studies. The CGH studies revealed abnormalities of chromosomes 1 and 13, and the results of LOH studies were consistent with the involvements of tumor suppressor genes from these regions. Family segregation studies mapped HPTPort to chromosome 1q22-q31 by establishing linkage with eight loci (D1S254, D1S222, D1S202, D1S238, D1S428, D1S2877, D1S422, and D1S412) (peak two-point LOD scores = 3. 46-5.14 at 0% recombination), and defined the location of HPT Port to a 21 cM region flanked centromerically by D1S215 and telomerically by D1S306. Thus, HPTPort has been mapped to chromosome 1q22-q31, and a characterization of this gene will help to elucidate further the mechanisms that are involved in the development of parathyroid tumors.